DAMAGE TO THE YELLOW LIGAMENT IN DEGENERATIVE DISEASES OF THE LUMBAR REGION OF THE SPINE - R. Israilov; B. Mamajonov; R.Sakatalieva. (Scholar Express Journals, 2023)
This study studied the pathomorphological changes that develop in the yellow ligament of the spinal canal in all types of degenerative diseases of the lumbar spine. Yellow body fragments covering the posterior border of the spinal canal were taken as Material. The results show that in some degenerative diseases of the lumbar spine, the yellow ligament has only undergone hypertrophy, while in others it has developed dystrophy, limescale, and in others it has ossification and deformity. Developing after hypertrophy, thickening, degenerative and inflammatory diseases of the yellow ligament of the spine, it begins with an increase in cysticitra cells around the blood vessels and in the intermediate tissue. Hypertrophy of the yellow ligament shows a sharp increase in collagen fibers, the development of the fibroelastosis process, the breakdown and destruction of elastic fibers, and a decrease in the amount of bialn
Keywords: spine; yellow ligament; degenerative diseases